Materialni ustavni zakon v slovenskem ustavnem redu - Štefanec, Iztok (Pravnik, 2015)
The Constitution of the Republic of Slovenia is not the only substantive constitutional act within the Slovene constitutional order. Another one is the Basic Constitutional Charter, while the constitutional body could, according to the Constitutional Court and legal theory, also adopt the Substantive Constitutional Act, which would regulate constitutional matters separately from the Constitution. The article takes the view that this is generally an erroneous assumption. The Constitution and Rules of Procedure of the National Assembly do not regulate the legal basis for adopting the Substantive Constitutional Act: neither as a framework act for regulating constitutional matters nor for special and individual cases (e.g. for a specific field or in the event of legitimate reasons). For this purpose, the Slovene competent authorities refer to legislative acts that are adopted by a qualified or (more commonly) by a simple majority. This act form is prescribed in more than 80 Articles of the Constitution. The retained regulation of relations on the constitutional level is also advisable from the perspective of ensuring the coherence of the constitutional order. Weaknesses typical for the technique of changing the constitution by amendments are also common in constitutional orders that regulate various constitutional matters with the help of substantive constitutional acts. This can lead to disparities and collisions between the constitutional norms, which are difficult to solve by means of interpretation, or in extreme cases, even to parallel constitutional systems. This considerably reduces legal security, predictability and can also weaken the stability of the constitutional order.
Keywords: constitution; človekove pravice; human rights; pravne norme; Slovenia; Slovenija; ustava; ustavno pravo